INTERACTION BETWEEN LECTURER AND STUDENT IN ANSWER-QUESTION PROCESS - Ekawati (Prodi Bimbingan Konseling Universitas Negeri Manado, 2023)
This research focused on types of questioning strategies used by the lecturers. Questioning strategies is important in learning process because there are several goals or objectives that must be achieved. Building a bond between Lecturers and Students, building an atmosphere in the classroom are an important references for Lecturers in teaching and learning process. Building interactions out of the classroom is something that is usually done. Asking questions in classroom is a threat that is feared by students because they feel nervous, afraid of getting the wrong answer and feel less confident in answering questions. This research was based on a study conducted at Al Amanah Jeneponto Institute, particularly in English Subject. This research involved English Lecturers. To collect the data, the researcher recorded teaching process that carried out by the lecturer in the classroom. The lecturer was recorded in one meeting for each lecturer and the data were obtained, transcribed, and analyzed based on Brown and Levinson (1987). The findings revealed that there were five types of Questioning Strategies used by the lecturers in teaching and learning process; there were, procedural question, affective question, structuring question, divergent question and convergent question